Removal of ammonium Ions from digested sludge fugate by using natural zeolite - Mažeikienė, Aušra; Valentukevičienė, Marina (Journal of Environmental Engineering and Landscape Management, 2016)
Wastewater treatment loadings with total nitrogen can increased by introducing fugate that is saturated with ammonium ions, generated when dewatering wastewater treatment sludge. In this article the possibility to reduce the concentration of ammonium ions in the fugate by the use of natural zeolite (Transcarpatian clinoptilolite) has been analysed. Lab-scale experiments were carried out with different particle sizes zeolite: 0.8–1.6 mm, 1.6–2.5 mm and 2.5–3.2 mm. At the first stage of the experiments, zeolite particles were mixed with fugate and left to settle until a 99% efficiency of ammonium ion removal was achieved. At the second stage, ammonium ions were removed from the fugate by filtering this liquid through zeolite where the 70–92% efficiency was achieved. Zeolite saturated with ammonium ions possibly can be used in agriculture as nitrogenous fertilizers. Obtained fertilizer grade of zeolite saturated with fugate can also be produced from the high ammonium nitrogen concentration side-streams separated from wastewater flow from sludge digestion processes. First published online: 18 May 2016